A efemeropterofauna do trecho ritral inferior do rio Campo Belo, Itatiaia, RJ: composição e distribuição, com aspectos biológicos e ecológicos das espécies de Americabaetis Kluge, 1992 (Insecta: Ephemeroptera: Baetidae) - Francischetti, Cesar Nascimento (2002)
Samples from Campo Belo River (22°281S; 44°34'W), municipality of Itatiaia, RJ, in different mesohabitats, was registered the occurrence of 22 species, distributed in the following genera (number of species between brackets) Americabaetis (2), Aturbina (1), Baetodes (1), Callibaetis (1), Camelobaetidius (2), Cloeodes (1), Paracloeodes (2) (Baetidae), Leptohyphes (2), Leptohyphodes (1), Tricorythopsis (3) Tricorythodes (1) (Leptohyphidae), Farrodes (1), Massartella (1), Miroculis (1), Thraulodes (1) and Ulmeritoides (1) (Leptophlebiidae). From monthly quantitative collections, taken from October 1999 to September 2000, 3.170 specimens were obtained, 1.002 from the riparian vegetation and 786 from litter from pools. The months with the highest number of individuals were November (595 nymphys) and October 1999 (480 nymphys). The two species of Americabaetis present, A. alphus and A. longetron were studied with major emphasis, amouting respectively to 384 specimens (riparian vegetation being the preferential substratum, with 353 specimens) and 143 specimens (litter from riffles being the preferential substratum the, with 97 specimens). The secondary production of A. alphus was 847.99 mg.m².year¹ and that of A. longetron was 13,549.757 mg.m· ².year ¹ dry weight, in their preferential substrates. A. alphus, in litter from riffles, presented significant correlations with monthly rainfall (R = -0,6418; p<0,05), depth (R = -0.8165; p<0,05) and electric conductivity (R = 0.7993; p<0,05). By its turn, A. longetron showed significant correlation with pH (R = 0.5784; p<0,05).